Matematik Jožef Jenko - Južnič, Stanislav (Obzornik za matematiko in fiziko, 2015)
Josef Jenko was one of the most important mathematicians of Habsburg Monarchy in Vormärz. He lectured in Ljubljana, Linz, Graz, and in Viennese University. He formatted a whole bunch of leading experts including the Polish professor Schulz who distinguished himself as professor of mathematics and astronomy in Ljubljana. Jenko is specially credited for his lifelong friendship with Jernej (Bartholomew) Kopitar.
Keywords: Jenko, Jožef, 1776-1858; slovenski matematiki; biografije